2000
DOI: 10.1007/s003470050524
|View full text |Cite
|
Sign up to set email alerts
|

Ultraschallbiomikroskopie bei Pigmentglaukom

Abstract: The results show that iridozonular contact does not exist in every patient with pigmentary glaucoma. Therefore, it seems possible that more than one pathogenic mechanism is involved in pigmentary glaucoma. In patients with iridozonular contact, however, laser iridotomy significantly reduces intraocular pressure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Pillunat LE et al 29 studied UBM in pigmentary glaucoma and effect of YAG iridectomy on anterior segment structures and IOP. The results show that irido-zonular contact does not exist in every patient with pigmentary glaucoma.…”
Section: Determining the Mechanism Of Secondary Glaucomamentioning
confidence: 99%
“…Pillunat LE et al 29 studied UBM in pigmentary glaucoma and effect of YAG iridectomy on anterior segment structures and IOP. The results show that irido-zonular contact does not exist in every patient with pigmentary glaucoma.…”
Section: Determining the Mechanism Of Secondary Glaucomamentioning
confidence: 99%
“…In our study, UBM was used to evaluate increased iris concavity and the presence of iridozonular contact upon accomodation in patients with pigment dispersion. Pillunat et al 12 reported that iridozonular contact was not present in every patient with pigmentary glaucoma and observed that intraocular pressure decreased with laser iridotomy only in pigmentary glaucoma cases with iridozonular contact. In our study, it was observed that UBM was frequently used to evaluate glaucoma cases (60.8%).…”
Section: Discussionmentioning
confidence: 99%